6(3x-4)=60

Simple and best practice solution for 6(3x-4)=60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(3x-4)=60 equation:


Simplifying
6(3x + -4) = 60

Reorder the terms:
6(-4 + 3x) = 60
(-4 * 6 + 3x * 6) = 60
(-24 + 18x) = 60

Solving
-24 + 18x = 60

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '24' to each side of the equation.
-24 + 24 + 18x = 60 + 24

Combine like terms: -24 + 24 = 0
0 + 18x = 60 + 24
18x = 60 + 24

Combine like terms: 60 + 24 = 84
18x = 84

Divide each side by '18'.
x = 4.666666667

Simplifying
x = 4.666666667

See similar equations:

| 2(y+4)=7(y-1) | | 1-X+X=11 | | 43/6/2 | | 4=2y+2x | | 3(3x+1)-4(2x-5)=5(x-1)-2(10-x) | | 5a+7b=9 | | 3x+5/4=2x+5 | | 3x^2-2y^2-4y-26=0 | | 5(x-3)=33 | | x^2/8 | | 6x=78-4x | | 6(x-2)-(x+1)=2 | | 10-2c=4c+11 | | -8-8-8v=2v+93 | | 30=2/5w | | 4p-8=8 | | 8-5x=3x+8 | | 2y/9=14 | | -2a+(7a-2)-[(-a)+3]= | | 15x=1/15 | | 6(5x+2)=18 | | 15x-4=11x-16 | | -2+9x=10x | | y-83=-79 | | 14-18y=7y | | 6a-5a=9 | | -A+4=6 | | x+qsrt(x-9)=21 | | (5x^4)+(3x^2)+3=0 | | x+sqrt(x-9)=21 | | 2c+7=9 | | 8x-20=5x+7 |

Equations solver categories